Library Buildings: a User’s Viewpoint - Line, Maurice B. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
There are many studies of users and their behaviour and needs, but very few studies of their likes and dislikes where buildings are concerned. Actually, we could get quite a lot of useful information by noting down every irritation we ourselves experience in libraries other than our own.